2020
DOI: 10.1007/s10620-020-06653-0
|View full text |Cite
|
Sign up to set email alerts
|

Putting Crohn’s on the MAP: Five Common Questions on the Contribution of Mycobacterium avium subspecies paratuberculosis to the Pathophysiology of Crohn’s Disease

Abstract: For decades, Mycobacterium avium subspecies paratuberculosis (MAP) has been linked to the pathogenesis of Crohn’s disease. Despite many investigations and research efforts, there remains no clear unifying explanation of its pathogenicity to humans. Proponents argue Crohn’s disease shares many identical features with a granulomatous infection in ruminants termed Johne’s disease and similarities with ileo-cecal tuberculosis. Both are caused by species within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The incidence of NTM disease in humans has increased dramatically over the past thirty years worldwide [ 26 ], and the majority of human NTM infections have been attributed to the M. avium complex [ 26 ]. Many reports also suggest that MAP may be an etiological factor in Crohn’s disease in humans [ 27 ]; however, it should be noted that these patients often fail to show improvement after anti-tuberculosis therapy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NTM disease in humans has increased dramatically over the past thirty years worldwide [ 26 ], and the majority of human NTM infections have been attributed to the M. avium complex [ 26 ]. Many reports also suggest that MAP may be an etiological factor in Crohn’s disease in humans [ 27 ]; however, it should be noted that these patients often fail to show improvement after anti-tuberculosis therapy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This subspecies also infects animals in the wild such as red deer, rabbits, or buffalo which raises serious ecological concerns [ 28 ]. In humans, MAP has been associated with a long list of inflammatory and autoimmune diseases: Crohn’s disease, sarcoidosis, Blau syndrome, Hashimoto’s thyroiditis, autoimmune diabetes (T1D), multiple sclerosis (MS), rheumatoid arthritis, lupus, and Parkinson’s disease [ 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The inhalation of aerosolized MAP-contaminated manure by women in the first four weeks of pregnancy, and intrauterine transmission to the embryo, may be responsible for the development of anencephaly in the fetus.…”
Section: T1d and Mycobacterium Avium Subsp ...mentioning
confidence: 99%
“…In one of the IBDs, Crohn's disease, an antibiotic combination targeting Mycobacterium avian subspecies paratuberculosis (MAP) infection has been reported to lead to long-term disease remission [147][148][149][150][151]. Agrawal et al [149] discuss recent promising data and addresses several common objections regarding MAP's role, making a compelling case for the involvement of MAP or similar species. It has also been suggested that other CIDs might be caused by MAP [152].…”
Section: Chronic Inflammatory Disease Featuresmentioning
confidence: 99%